0083 Occupational Injuries at the Community Level. (23rd June 2014) - Forst, Linda; Chin, Brian; Friedman, Lee
Abstract : Objectives: Low wage and immigrant workers suffer an excess of injuries and are often difficult to reach. There is a need to identify alternative forums for health and safety training. The aim of this study was to determine whether injured workers cluster by geographic area; this would serve as a basis for targeting occupational health and safety interventions at the community level. Method: Work-related injuries from the Illinois Trauma Registry were extracted and mapped by residential zipcode for 2000–2009. Injury data was merged with employment data. Results: There were 23 200 work-related injuries. Of the 1382 zipcodes, 79.3% of the injuries occurred among residents living in 20% of the zipcodes. 21.2% of the work-related injuries (N = 4914) occurred in the 25 zipcodes with the highest counts. We identified six spatial clusters. In the 25 ZIP codes with the highest rates of injuries among employed persons, less than 1% of the injuries occurred in these zipcodes (N = 99). Conclusions: Training at the community level could reduce workplace injury and is needed to augment the void in workplace training. Alternative datasets, not originally designed for occupational surveillance, could be useful for identifying communities with occupational injury and illness clusters. The validity and usefulness of these datasets should be further assessed, and the communities in which these clusters occur should be mapped to identify community level infrastructure that could be leveraged for training interventions. A bridge should be created between occupational medicine, governmental institutions, social work and community advocacy in order to make a community intervention program viable.